2008
DOI: 10.1007/s00508-008-0972-y
|View full text |Cite
|
Sign up to set email alerts
|

Hospital antibiotic management in Hungary – results of the ABS maturity survey of the ABS International group

Abstract: Antibiotic stewardship cannot be conducted without appropriate resources (time, financing) provided by hospital management or the authorities. The technical background (microbiology, organizations, etc.) on which to build is already available in Hungarian hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…It is not surprising that obese and lean people would have different microbiota profiles since the gut microbiota play such an important role in converting food into energy (Bäckhed et al, 2004). Ternak et al (2008) suggested that the wide-spread usage of antibiotics may be a large factor in the obesity epidemic of humans. As growth promotants in animals, the mechanism of the growth promoting effect of antibiotics is supposedly associated with the inhibition of the microbiota of the animals by the antibiotics, but the exact mechanism is unknown (Gaskins et al, 2002).…”
Section: Probiotics Cardiac Health and Obesitymentioning
confidence: 99%
“…It is not surprising that obese and lean people would have different microbiota profiles since the gut microbiota play such an important role in converting food into energy (Bäckhed et al, 2004). Ternak et al (2008) suggested that the wide-spread usage of antibiotics may be a large factor in the obesity epidemic of humans. As growth promotants in animals, the mechanism of the growth promoting effect of antibiotics is supposedly associated with the inhibition of the microbiota of the animals by the antibiotics, but the exact mechanism is unknown (Gaskins et al, 2002).…”
Section: Probiotics Cardiac Health and Obesitymentioning
confidence: 99%
“…In addition, the cost-effectiveness of these programs has not been evaluated at this time. The extensive literature published on programs in other EU member states further underlines the need for consensus development on best practice in Europe [20][21][22][23][24][25].…”
Section: Special Report Allerberger Gareis Jindrák and Struelensmentioning
confidence: 99%